The Fibrin Assay Comparison Trial (FACT) - Dempfle, Carl-Erik; Zips, Sybille; Ergül, Hanimsah; Heene, Dieter L.; FACT study group (Thrombosis and Haemostasis, 2001)
Although D-dimer has gained widespread clinical use as a parameter for detection of in vivo fibrin formation, the issue of standardization of D-dimer assays remains to be resolved. The FACT study was performed to generate basic data for development of calibrators and standard preparations.A set of 86 samples, including plasma samples from patients with DIC, DVT, and other clinical conditions, serial dilutions of pooled plasma samples, and plasma samples containing fibrinogen- and fibrin derivatives, were distributed to 12 manufacturers of D-dimer assays.D-dimer assays differ concerning specificity for crosslinked fibrin, and preference for either high molecular weight fibrin complexes, or low molecular weight fibrin degradation products. Terminal plasmin digests of fibrin clots for calibration produce aberrant results in some assays, especially those with preference for high molecular weight crosslinked fibrin derivatives. The best conformity is achieved by the use of pooled plasma samples from patients with high levels of D-dimer antigen in plasma. In vitro preparations containing a comparable composition of fibrin derivatives to clinical plasma samples may also serve as reference material.
Keywords: Fibrinogen-fibrin degradation products; D-dimer; fibrinogen; fibrin; standardization